Widening mental health and substance use inequities among sexual and gender minority populations: Findings from a repeated cross-sectional monitoring survey during the COVID-19 pandemic in Canada. (January 2022) - Slemon, Allie; Richardson, Chris; Goodyear, Trevor; Salway, Travis; Gadermann, Anne; Oliffe, John L.; Knight, Rod; Dhari, Shivinder; Jenkins, Emily K.
Highlights: The COVID-19 pandemic affects sexual and gender minorities' (SGMs) mental health. SGMs experience disproportionate mental health outcomes compared to non-SGMs. SGMs further experience disproportionate substance use impacts. Pre-existing mental health conditions contribute to mental health impacts for SGMs. Abstract: This paper examines the mental health and substance use impacts of the COVID-19 pandemic among sexual and gender minority (SGM) populations as compared to non-SGM populations, and identifies risk factors for mental health and substance use impacts among SGM groups. Data were drawn from two rounds of a repeated cross-sectional monitoring survey of 6027 Canadian adults, with Round 1 conducted May 14–19, 2020 and Round 2 conducted September 14–21, 2020. Bivariate cross-tabulations with chi-square tests were utilized to identify differences in mental health and substance use outcomes between SGM and non-SGM groups. Separate multivariable logistic regression models were used to identify risk factors for mental health and substance use outcomes for all SGM respondents. Compared to non-SGM respondents, a greater proportion of SGM participants reported mental health and substance use impacts of the COVID-19 pandemic, including deterioration in mental health, poor coping, suicidal thoughts, self-harm, alcohol and cannabis use, and use of substances to cope. Among SGM respondents, various risk factors, including having a pre-existing mental health condition, were identified as associated with mental health and substance use impacts. These widening inequities demonstrate the need for tailored public mental health actions during and beyond the pandemic.